2019
DOI: 10.7752/jpes.2019.02180
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Competitive anxiety is related to athletes' performance. Due to this, it is important to maintain it on an optimal level. While anxiety has a well-studied gender difference that is related to the opposite patterns of activity in left parietal and temporal lobes, dorsomedial prefrontal cortex, cerebellum, and occipital gyrus, gender differences in competitive anxiety and its factors are not fully investigated. Exploratory research of competitive anxiety and coping strategies in Ukrainian junior handball nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Regarding gender differences in the mental skills of handball players, the obtained results indicate that female handball players show a lower degree of anxiety regulation ability than 10.3389/fpsyg.2022.960201 male handball players but, on the other hand, show a higher degree of relaxation ability. The obtained results are in line with previous research, which found that female handball players have a somewhat lower ability to regulate emotions and less coping strategies compared to male handball players (Kristjánsdóttir et al, 2018;Ivaskevych et al, 2019;Ökrös et al, 2020). Although the results on gender differences in mental skills are inconsistent, what can be noticed is those female handball players have a higher degree of emotional arousal, which does not have to be a consequence of personality traits, but the situation itself, and that aspects of competitive anxiety and performance concerns are more present with them than with male handball players.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding gender differences in the mental skills of handball players, the obtained results indicate that female handball players show a lower degree of anxiety regulation ability than 10.3389/fpsyg.2022.960201 male handball players but, on the other hand, show a higher degree of relaxation ability. The obtained results are in line with previous research, which found that female handball players have a somewhat lower ability to regulate emotions and less coping strategies compared to male handball players (Kristjánsdóttir et al, 2018;Ivaskevych et al, 2019;Ökrös et al, 2020). Although the results on gender differences in mental skills are inconsistent, what can be noticed is those female handball players have a higher degree of emotional arousal, which does not have to be a consequence of personality traits, but the situation itself, and that aspects of competitive anxiety and performance concerns are more present with them than with male handball players.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have found that female football players react and perceive more intense stress and that they experience less control in stressful situations (Kaiseler et al, 2012). Similarly, in the sample of junior female handball players of the Ukrainian national team, the result shows that female handball players achieve higher scores on competitive anxiety and are more prone to selfblame compared to male handball players (Ivaskevych et al, 2019). In the sample of the junior Hungarian handball team, the authors found that male handball players achieved significantly higher scores on Coping with Adversity and Freedom from worry, while female handball players scored higher scores on Goal Setting/Mental Preparation and Coachability (Ökrös et al, 2020).…”
Section: General Attitude/ Mindset Dimensionmentioning
confidence: 86%
“…Handball is a situational sport with a pronounced risk of injury, which requires a high level of strength and mobility of nervous processes, the resistance of the central nervous system to interference in conditions of significant nervous and emotional tension, control and self-control [20,18,19].…”
Section: Discussionmentioning
confidence: 99%